2011
DOI: 10.1017/s0033291711001206
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy as guided self-help for psychological distress and positive mental health: a randomized controlled trial

Abstract: The ACT-based self-help programme with minimal email support is effective for people with mild to moderate depressive symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
155
5
20

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(189 citation statements)
references
References 44 publications
9
155
5
20
Order By: Relevance
“…Ethical approval was obtained from the host university ethics committee and participants received an information sheet and gave their consent before taking part Participants A power calculation using G*Power (Faul, Erdfelder, Lang & Buchner, 2007) with p=.05 and power set at 80% showed that 68 participants would be needed to detect comparable effect sizes to those reported in a similar study of ACT bibliotherapy in a nonclinical sample (Fledderus et al, 2011). Eighty student participants were recruited to allow for up to 15% attrition.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical approval was obtained from the host university ethics committee and participants received an information sheet and gave their consent before taking part Participants A power calculation using G*Power (Faul, Erdfelder, Lang & Buchner, 2007) with p=.05 and power set at 80% showed that 68 participants would be needed to detect comparable effect sizes to those reported in a similar study of ACT bibliotherapy in a nonclinical sample (Fledderus et al, 2011). Eighty student participants were recruited to allow for up to 15% attrition.…”
Section: Designmentioning
confidence: 99%
“…However, while there is evidence that self-help cognitive behavioural therapy (CBT-SH) is effective for depression (Gregory, Canning, Lee & Wise, 2004) and anxiety disorders (Lewis, Pearce & Bisson, 2012), little is known about the effectiveness of MBCT-SH. Although research into MBCT-SH is in its infancy, there is emerging evidence that self-help books based on Acceptance and Commitment Therapy (ACT), an approach which includes mindfulness principles, can improve anxiety and depression in community (Fledderus, Bohlmeijer, Pieterse & Schreurs, 2011) and student (Muto, Hayes & Jeffcoat, 2011) populations. Similarly, a recent meta-analysis of self-help interventions that included mindfulness and/or acceptance components found they led to significantly lower symptoms of anxiety and depressive in comparison to control conditions (Cavanagh, Strauss, Forder & Jones, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…El origen de los participantes fue EEUU en 17 estudios con sus seguimientos (Clarke et al, 1995(Clarke et al, , 2001Garber et al, 2009;Gillham et al, 2006;Le et al, 2011;Lynch et al, 1997;Mossey et al, 1996;Muñoz et al, 2007;Puskar et al, 2003;Seligman et al, 1999Seligman et al, , 2007Stice et al, 2006Stice et al, , 2008Stice et al, , 2010Van Voorhees et al, 2008Young et al, 2006Young et al, , 2010Zlotnick et al, 2001); Holanda en siete estudios (Allart-van Dam et al, 2003Dozeman et al, 2012;Korte et al, 2012;Fledderus et al, 2012;Van´t Veer-Tazelaar et al, 2009Westerhof et al, 2010;Willemse et al, 2004); Australia en cuatro estudios (Roberts et al, 2003(Roberts et al, , 2004Sheffield et al, 2006; Spence et al, 2003;Stamp et al, 1995); España en tres estudios (González et al, 2006;Vázquez et al, 2012Vázquez et al, , 2013; Canadá en dos estudios (Dobson et al, 2010;Konnert et al, 2009); China en un estudio (Liu et al, 2009); México en un estudio (Lara et al, 2010); e Islandia en un estudio (Arnarson y Craighead, 2009 (Allart-van Dam et al, 2003…”
Section: Resultados Descripción De Los Estudiosunclassified
“…Mood 89 (Liu et al, 2009); un estudio empleó terapia de apoyo y expresión (Stamp et al, 1995); dos estudios utilizaron un programa de terapia de revisión de vida 910 (Korte et al, 2012;Westerhof et al, 2010) (Van Voorhees et al, 2008; un estudio empleó terapia de aceptación y compromiso (Fledderus et al, 2012); un estudio empleó una aproximación escalonada con observación, programación de actividades, revisión de vida y consulta con el médico general (Dozeman et al, 2012); mientras que otros ocho estudios no son tan concretos y simplemente especifican que se fundamentan en componentes cognitivo-conductuales (Garber et al, 2009;Sheffield et al, 2006;Seligman et al, 1999Seligman et al, , 2007Stice et al, 2006Stice et al, , 2008Stice et al, , 2010, técnicas cognitivo-conductuales junto con potenciación de recursos personales y apoyo social (González et al, 2006); o cognitivo-conductuales y evolutivos (Arnarson y Craighead, 2009.…”
Section: Resultados Descripción De Los Estudiosunclassified
“…Instead, it emphasizes learning new ways to accommodate difficult thoughts and feelings -primarily through mindfulness approaches -without letting them dominate, while guiding people to take proactive steps towards living in a way that is consistent with their values. ACT has been shown to be useful for a range of mental health issues 10 and has been used successfully in a guided self-help format 11 .…”
mentioning
confidence: 99%